The Influence Of Medicinal Plant Literacy Through Youtube Media On Ecological Intelligence Via The PBL Model In Social Studies Subjects (Quasi-Experiment At Mts Miftahul Huda Majalengka) - Syaoqi Akbari Jamaludin; Nana Supriatna; Neiny Ratmaningsih (Eduvest - Journal of Universal Studies, 2024)
Ecological intelligence will be closely related to the environment in which humans live. Nowadays, ecological intelligence is very necessary in various aspects of human life, this is because many people in human life today pay little attention to the state of the environment. The school not only creates smart students, but also tries to create students who have the character as stated in the 2013 curriculum, especially regarding students' concern for the environment. Human interaction with the environment causes a lot of damage to the environment itself. This research aims to determine the picture of medicinal plant literacy in the school environment on students' ecological intelligence in social studies subjects and to find out how much influence medicinal plant literacy in the school environment has on students' ecological intelligence in social studies subjects. This research is quasi-experimental research, using quantitative data analysis. The sample in this study was 281. The results of this research are that literacy of medicinal plants in the school environment as a learning resource can increase students' ecological intelligence in social studies subjects. Previously, the majority of students had a moderate level of ecological intelligence, but after being given treatment, there was a significant increase, especially in the level of ecological intelligence which became higher and literacy of medicinal plants in the school environment as a learning resource had a significant effect on increasing students' ecological intelligence in social studies subjects.